Physicians' Opinion and Practice With the Continuous Use of Sedatives in the Last Days of Life - Heijltjes, Madelon T.; Morita, Tatsuya; Mori, Masanori; Heckel, Maria; Klein, Carsten; Stiel, Stephanie; Miccinesi, Guido; Deliens, Luc; Robijn, Lenzo; Stone, Patrick; Sykes, Nigel; Hui, David; et al. (Journal of Pain and Symptom Management, 2021)
Context: There are few international studies about the continuous use of sedatives (CUS) in the last days of life. Objectives: We aim to describe the experiences and opinions regarding CUS of physicians caring for terminally ill patients in seven countries. Methods: Questionnaire study about practices and experiences with CUS in the last days of life among physicians caring for terminally ill patients in Belgium (n = 175), Germany (n = 546), Italy (n = 214), Japan (n = 513), the Netherlands (n = 829), United Kingdom (n = 114) and Singapore (n = 21). Results: The overall response rate was 22%. Of the respondents, 88-99% reported that they had clinical experience of CUS in the last 12 months. More than 90% of respondents indicated that they mostly used midazolam for sedation. The use of sedatives to relieve suffering in the last days of life was considered acceptable in cases of physical suffering (87%–99%). This percentage was lower but still substantial in cases of psycho-existential suffering in the absence of physical symptoms (45%–88%). These percentages were lower when the prognosis was at least several weeks (22%–66% for physical suffering and 5%–42% for psycho-existential suffering). Of the respondents, 10% or less agreed with the statement that CUS is unnecessary because suffering can be alleviated with other measures. A substantial proportion (41%–95%) agreed with the statement that a competent patient with severe suffering has the right to demand the use of sedatives in the last days of life. Conclusion: Many respondents in our study considered CUS acceptable for the relief of physical and psycho-existential suffering in the last days of life. The acceptability was lower regarding CUS for psycho-existential suffering and regarding CUS for patients with a longer life expectancy.
CRIS-Team Scopus Importer:2021-10-22
Keywords: Continuous use of sedatives; Deep sedation; End of life care; Palliative care; Palliative sedation; Questionnaire study